Mine filling cement material capable of cementing high-content phosphate tailings as well as preparation method and use method of mine filling cement material

Through pretreatment of phosphogypsum and reasonable formulation design, combined with active blends, the problem that the mine filling cement material cannot shorten the settling time while reducing the water secretion rate, achieving a high-strength, low-cost and environmentally friendly mine filling effect.

CN119528536APending Publication Date: 2025-02-28SICHUAN LOMON IND GYPSUM DEV CO LTD

Patent Information

Application Number
CN202411725055.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing mine filled cement materials cannot shorten the settling time while reducing the water secretion rate and improving the material strength.

Method used

Pretreatment of phosphogypsum by flotation, water washing and calcination will improve its specific surface area and gelling performance. Combined with active blends such as slag, metakaolin, yellow phosphorus slag, etc., a reasonable formula is designed to increase the exciter and mineral blends to shorten the settling time and improve strength.

Benefits of technology

It effectively shortens the condensation time, reduces the water secretion rate, improves the early and later strength of the filling materials, meets the requirements of mine recovery, reduces the underground drainage and filling costs, and reduces pollution to the water environment in the mine area.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention provides a mine filling cement material capable of cementing high-content phosphate tailings as well as a preparation method and a use method thereof, relates to the technical field of mine filling materials, and solves the technical problems that the existing mine filling cement material cannot shorten the setting time and improve the setting strength of the material while reducing the bleeding rate. The high-strength concrete is prepared from the following components: 40 to 45 weight percent of slag, 7 to 10 weight percent of metakaolin, 8 to 10 weight percent of yellow phosphorus slag, 0 to 5 weight percent of phosphogypsum, 35 to 40 weight percent of cement clinker, 1 to 5 weight percent of exciting agent and 1 to 5 weight percent of mineral admixture, the mineral admixture is prepared from bentonite, sepiolite and attapulgite. According to the invention, the setting time can be effectively shortened, the bleeding rate is effectively reduced, the filling time is shortened, the underground drainage and filling cost is reduced, the pollution to the water environment of a mining area is reduced, the effective utilization of the phosphate tailings is realized, and the stacking of the phosphate tailings and the environmental pollution are reduced; the condensation speed and the strength of the filling body can be effectively improved; the comprehensive performance of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mine filling materials, and in particular to a mine filling cement material capable of cementing high-dosage phosphate tailings and a preparation method and use method thereof. Background Art

[0002] With the development of society, the development and utilization of phosphate ore has increased. Phosphate ore is enriched through beneficiation, and a large amount of phosphorus-containing waste, namely phosphate tailings, is produced. The storage of phosphate tailings will not only occupy a large amount of land, but also cause serious environmental pollution. Cement, as a traditional cementitious material, was widely used in major mines in early filling, and the method was simple. With the decrease in the fineness of phosphate tailings, it is difficult to dehydrate the phosphate tailings slurry, and it is difficult to increase the slurry concentration, resulting in a large amount of water seepage, unstable setting time and rheological properties of the filling body in a single cement filling, further leading to groundwater environmental pollution, "sugar core" in the mine, and filling without top connection, causing a series of environmental and safety problems. At the same time, with the production restrictions in the cement industry, the filling cost has gradually increased. With the vigorous development of mineral development activities, different mines have put forward different requirements for filling processes and technologies. In order to further reduce costs and meet the needs of mine development, the types of mine filling materials are increasing, which are mainly divided into two categories: one is the main body of the slurry, which is the aggregate supporting the skeleton, usually tailings, waste rock, etc.; the second is the cementitious material that plays the role of aggregate gelling and solidification. It is one of the main reasons affecting the strength of the filling body. Commonly used ones can be divided into traditional cementitious materials, such as cement, and new cementitious materials. At present, the research is mainly devoted to the development of new cementitious materials. It is crucial for mines to achieve economical and efficient mining by choosing reasonable types of cementitious materials and reducing the amount of cementitious materials while meeting the needs of mine filling. The new cementitious materials for mines mainly include alkali-activated cementitious materials, high-water materials, and cement powder.

[0003] Alkali-activated cementitious materials refer to a type of cementitious materials formed by the reaction of raw materials with volcanic ash activity or potential hydraulic hardness with alkaline activators. Such materials are mostly made of aluminosilicate minerals as the main raw materials, and common industrial solid wastes include slag, steel slag, fly ash and red mud. Alkaline activators generally refer to caustic soda, silicates containing alkaline elements, aluminates, phosphates, sulfates, carbonates and other substances. Commonly used in industry are lime, gypsum, cement clinker, etc.

[0004] High water-repellent material is composed of two solid powders, A and B. A is composed of aluminate or sulphoaluminate with a variety of admixtures that have a retarding and adjusting effect, and B is mainly composed of gypsum, lime, clay and accelerators. The mass water-solid ratio of high water solidification body is 2.5-3:1, and the volume water content can reach 90%, so it is called high water material. It has stable rheology, constant resistance and other mechanical properties, and is a good engineering filling support material.

[0005] Cement powder is a new type of binder that has developed relatively maturely. It mainly uses industrial waste residues such as blast furnace water-quenched slag as raw materials. By adding a small amount of stimulating materials, the potential activity of the industrial waste residues is activated to produce hydraulic cementation. The core technology is the selection and component ratio of active stimulating materials or stimulants.

[0006] Alkali-activated cementitious materials, high-water materials, cement powder and other new cementitious materials for mines have many different proportions due to the different selection of various active materials and activators. Existing new cementitious materials need to be used as mine filling materials in a higher proportion, which will reduce the fluidity of the filling body, and additional drag reducers need to be added to improve the fluidity of the filling body. In addition, the most commonly used active material is blast furnace slag. With the tightening of national environmental protection policies, the cost of using blast furnace slag in my country has increased year by year, resulting in an increase in the cost of filling cementitious materials based on slag.

[0007] For example, the patent with publication number CN103964804A proposes a low-bleeding rate pumpable phosphogypsum and yellow phosphorus slag filling paste and preparation method, which uses industrial waste phosphogypsum as filling aggregate and adds a certain proportion of yellow phosphorus slag as cementing material. The filling paste has precise concentration control, low bleeding rate, good fluidity, certain early strength and good medium- and long-term strength, and is used for paste filling in underground goafs of phosphate mines, reducing the bleeding rate of phosphogypsum underground cementing filling slurry, reducing the cost of underground drainage and filling, and reducing pollution to the water environment in the mining area. However, the phosphogypsum is simply dried to lose its crystal water, and only uses its own certain cementing properties combined with the certain cementing properties of yellow phosphorus slag to replace cement. Although it can reduce the bleeding rate and have good fluidity, it takes a long time to set and has a relatively low final strength. Summary of the invention

[0008] The invention provides a mine filling cement material capable of cementing high-content phosphate tailings and a preparation and use method thereof, so as to solve the technical problem that the existing mine filling cement material cannot simultaneously shorten the setting time and improve the material strength while reducing the water seepage rate.

[0009] The embodiments of the present invention are implemented by the following technical solutions:

[0010] A mine filling cement material capable of cementing high-content phosphate tailings comprises the following components based on 100wt% of the mass of the mine filling cement material: 40wt% to 45wt% of slag, 7wt% to 10wt% of metakaolin, 8wt% to 10wt% of yellow phosphorus slag, 0wt% to 5wt% of phosphogypsum, 35wt% to 40wt% of cement clinker, 1wt% to 5wt% of an activator and 1wt% to 5wt% of a mineral admixture; the mineral admixture comprises bentonite, sepiolite and attapulgite.

[0011] Preferably, the specific surface area of ​​the phosphogypsum is ≥300m 2 / kg.

[0012] Preferably, the activator is at least two of sodium silicate, aluminum sulfate, calcium oxide and calcium hydroxide.

[0013] Preferably, the activator is a combination of one of sodium silicate and aluminum sulfate and at least one of calcium oxide and calcium hydroxide.

[0014] Preferably, based on 100wt% of the mass of the mineral admixture, the mineral admixture includes 15wt% to 25wt% of bentonite, 25wt% to 35wt% of sepiolite and 45wt% to 55wt% of attapulgite.

[0015] Preferably, the particle size of the component materials is ≥200 mesh, and the slag uses slag powder of S95 or above.

[0016] A method for preparing a mine filling cement material capable of cementing high-dosage phosphate tailings comprises the following steps:

[0017] S1: Pretreatment: flotation, washing and calcination of phosphogypsum;

[0018] S2: mixing and grinding slag, metakaolin, yellow phosphorus slag, phosphogypsum and cement clinker to obtain a cementitious material;

[0019] S2: 1wt% to 5wt% of an activator and 1wt% to 5wt% of a mineral admixture are mixed with a cementitious material and then ground to obtain a mine filling cement.

[0020] Preferably, the step S1 includes the following specific steps:

[0021] S1.1: Flotation: Mix phosphogypsum and water at a ratio of 1:2-3 to prepare a slurry, add a flotation agent, and feed it into a flotation machine. After multiple flotations, the solid and liquid are separated, and the filter cake is the preliminarily purified phosphogypsum;

[0022] S1.2: Water selection: The phosphogypsum filter cake after flotation is mixed with water at a ratio of 1:2-3 to prepare a slurry, which is then washed with water for multiple times before solid-liquid separation. The filter cake is further purified phosphogypsum;

[0023] S1.3: Calcination: The washed phosphogypsum filter cake is sent to a drying device for low-temperature drying at 100°C to 150°C to remove surface moisture. After drying to a moisture content of the phosphogypsum of less than 1%, it is sent to a calcining furnace for calcination at 600°C to 800°C for 1h to 2h, and then naturally cooled to room temperature to obtain the final purified phosphogypsum product.

[0024] Preferably, in step S1.2, the water washing process is repeated several times until the soluble salt content in the phosphogypsum is ≤2%.

[0025] A method for using a mine filling cement material capable of cementing high-dosage phosphate tailings comprises the following steps:

[0026] T1: preparing the phosphate tailings into a phosphate tailings slurry with an underflow concentration of 66% to 68%;

[0027] T2: mixing the mine filling cement material and the phosphate tailings slurry at a ratio of 1:7.2-8.8 to obtain a mixed filling material;

[0028] T3: Sending mixed fill material into the mine.

[0029] Preferably, in step T3, after the mixed filler is sent into the mine, the setting time is ≤2d, and the compressive strength meets the cementation time required for mine recovery is ≤28d.

[0030] By adopting this technical solution, the specific surface area of ​​phosphogypsum can reach 300m 2 / kg or more, which improves its activity and gelling properties. This not only solves the disposal problem of phosphogypsum, but also converts it into a valuable building material. While providing certain gelling properties, phosphogypsum can also rely on its good water absorption to effectively shorten the setting time, effectively reduce the water seepage rate, shorten the filling time, reduce the cost of underground drainage and filling, reduce the pollution to the water environment in the mining area, realize the effective utilization of phosphate tailings, and reduce the stacking and environmental pollution of phosphate tailings.

[0031] Through reasonable formula design and pretreatment of phosphogypsum, the filling material can have good gelling properties, can condense and reach a high recovery strength in a short time, and meet the requirements of mine recovery. Pretreatment of phosphogypsum removes soluble salts in phosphogypsum, such as free phosphoric acid and fluoride, which will affect the gelling properties of phosphogypsum; at high temperature, dihydrate gypsum (CaSO4·2H2O) in phosphogypsum is dehydrated to form β-type hemihydrate gypsum (CaSO4·0.5H2O), calcined to remove crystal water, and β-type hemihydrate gypsum is generated to improve its stability and reactivity; and β-type hemihydrate gypsum has good gelling properties, can be rehydrated to form dihydrate gypsum after adding water, forming a solid gel, thus having excellent gelling properties. The calcined phosphogypsum has better chemical stability, is not easily affected by environmental factors, and is suitable for long-term use. On the basis of reaching the recovery strength, it only needs 28 days of cementation and maintenance, which ensures the safety and stability of the mine while shortening the construction period and improving the construction efficiency. The particle size of the material is less than 200 mesh, which ensures good fluidity and pumpability, and is easy to mix and construct. By adding active admixtures such as slag, metakaolin, and yellow phosphorus slag, the amount of cement clinker used is reduced, and the production cost is reduced. The utilization of industrial waste residues such as slag and yellow phosphorus slag not only reduces the cost of waste treatment, but also reduces the production cost of materials.

[0032] The filling fluidity of phosphogypsum is strong, and the slurry is not easy to settle during pipeline transportation. It can meet the requirements of paste transportation when combined with yellow phosphate rock, and can reduce the water bleeding rate. In addition, phosphogypsum and yellow phosphate rock are only used as partial replacements of cementitious materials to improve the cementing speed and fluidity. The filling material still mainly relies on cement clinker as the main cementitious material, which has stable performance and mature technology, and can ensure the consistency and reliability of the filling material. The cement feed combined with slag and metakaolin can effectively improve the early setting strength, and has little effect on fluidity and water bleeding rate.

[0033] Slag has high activity and can undergo secondary hydration reaction with the hydration products in cement to generate more calcium silicate hydrate (CSH) gel, thereby improving the early strength of the filling material; slag can also improve the corrosion resistance and impermeability of the filling material and extend its service life. The fineness of slag is generally high, which can improve the fluidity of the filling material and make it easier to pump and construct; the main components of kaolin are amorphous silicon dioxide and aluminum oxide, which have high volcanic ash activity and can react with the hydration products in cement to generate more calcium silicate hydrate (CSH) gel, thereby improving the early strength of the filling material; it can refine the pore structure of the filling material, improve its density and compactness, thereby improving its mechanical properties and durability; it can reduce the porosity of the filling material, improve its impermeability, and prevent the invasion of moisture and harmful substances; kaolin can improve the corrosion resistance of the filling material and extend its service life.

[0034] After mixing and grinding the above components, add the activator and the mineral admixture mixed powder to obtain the mine filling cement. The activator can activate the activity of SiO2 and CaO in the yellow phosphorus slag, and can promote the chemical substances of the hydration reaction of cement or other cementitious materials, improve the early strength and late strength of the filling material, and improve its performance. Bentonite is a clay mineral with montmorillonite as the main component, sepiolite is a fibrous mineral with magnesium silicate as the main component, and attapulgite is a clay mineral with silicate as the main component, all of which have good water absorption and expansion. It can improve the fluidity of the filling material, making it easier to pump and construct; it can absorb excess water, reduce the water bleeding rate of the filling material, and improve its density and uniformity; it can improve the microstructure of the filling material, improve its stability and crack resistance; it can improve the impermeability and corrosion resistance of the filling material and extend its service life.

[0035] Through reasonable formula design, the synergistic effect of multiple active admixtures is achieved, and the comprehensive performance of the material is improved. The flotation, washing and calcination pretreatment technology of phosphogypsum effectively removes impurities and improves its activity and gelling properties. The resource utilization of phosphogypsum and phosphate tailings not only solves the problem of waste disposal, but also generates economic benefits.

[0036] The present invention provides a high-performance, low-cost, and environmentally friendly mine filling cement material by comprehensively utilizing phosphogypsum and phosphate tailings. The material not only solves the problem of waste disposal, but also improves the safety and stability of the mine, and has significant economic and social benefits.

[0037] The technical solution of the embodiment of the present invention has at least the following advantages and beneficial effects:

[0038] 1. The present invention can effectively shorten the setting time, effectively reduce the water seepage rate, shorten the filling time, reduce the cost of underground drainage and filling, reduce the pollution to the water environment in the mining area, realize the effective utilization of phosphate tailings, and reduce the stacking of phosphate tailings and environmental pollution;

[0039] 2. The present invention can effectively improve the early coagulation strength and coagulation speed;

[0040] 3. The present invention improves the comprehensive performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0042] Figure 1 A flow chart of the preparation method and use method of a mine filling cement material capable of cementing high-dosage phosphate tailings provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0044] Example 1

[0045] A mine filling cement material capable of cementing high-content phosphate tailings comprises the following components based on 100wt% of the mass of the mine filling cement material: 42wt% of slag, 8wt% of metakaolin, 9wt% of yellow phosphorus slag, 2wt% of phosphogypsum, 37wt% of cement clinker, 1wt% of an activator and 1wt% of a mineral admixture; the mineral admixture comprises bentonite, sepiolite and attapulgite.

[0046] In this embodiment, the phosphogypsum is pre-treated by flotation, washing and calcination, and its specific surface area is 300m 2 / kg.

[0047] In this embodiment, the activator is sodium silicate and calcium hydroxide added in a ratio of 1:1.

[0048] In this embodiment, based on 100 wt% of the mineral admixture, the mineral admixture includes 20 wt% of bentonite, 30 wt% of sepiolite and 50 wt% of attapulgite.

[0049] In this embodiment, the particle size of the component materials is ≥200 mesh, and the slag uses S95 slag powder.

[0050] A method for preparing a mine filling cement material capable of cementing high-content phosphate tailings comprises the following steps:

[0051] S1: Pretreatment: flotation, washing and calcination of phosphogypsum;

[0052] S1.1: Flotation: Mix phosphogypsum and water in a ratio of 1:3 to prepare a slurry, add a flotation agent, and feed it into a flotation machine. After multiple flotations, the solid and liquid are separated, and the filter cake is the preliminarily purified phosphogypsum;

[0053] S1.2: Water separation: The phosphogypsum filter cake after flotation is mixed with water at a ratio of 1:3 to prepare a slurry, which is washed with water for multiple times and then separated into solid and liquid. The filter cake is further purified phosphogypsum; the water washing process is repeated until the soluble salt content in the phosphogypsum is ≤2%

[0054] S1.3: Calcination: The washed phosphogypsum filter cake is sent to a drying device for low-temperature drying at 100°C to remove surface moisture. After drying to a moisture content of the phosphogypsum of less than 1%, it is sent to a calcining furnace and calcined at 700°C for 2 hours, and then naturally cooled to room temperature to obtain the final purified phosphogypsum product.

[0055] S2: 42 wt% of slag, 8 wt% of metakaolin, 9 wt% of yellow phosphorus slag, 2 wt% of phosphogypsum, and 37 wt% of cement clinker are mixed and ground to obtain a cementitious material;

[0056] S2: 1 wt% of an activator and 1 wt% of a mineral admixture are mixed with a cementitious material and then ground to obtain a mine filling cement.

[0057] A method for using a mine filling cement material capable of cementing high-dosage phosphate tailings comprises the following steps:

[0058] T1: The phosphate tailings are prepared into a slurry with an underflow concentration of 66%;

[0059] T2: mixing the mine filling cement material and the phosphate tailings slurry at a ratio of 1:8;

[0060] T3: Sending mixed fill material into the mine.

[0061] In this embodiment, in step T3, after the mixed filling material is sent into the mine, the setting time is 2 days, and the compressive strength meets the cementing time requirement of mine recovery of ≤28 days.

[0062] In this embodiment, the relevant data is designed based on the requirement of a mine that the 28d compressive strength is ≥1.8MPa.

[0063] Example 2

[0064] The only difference between this embodiment and Embodiment 1 is that a mine filling cement material that can cement high-doped phosphate tailings includes the following components, based on the mass of the mine filling cement material as 100wt%,: 43wt% of slag, 9wt% of kaolin, 8wt% of yellow phosphorus slag, 1wt% of phosphogypsum, 37wt% of cement clinker, 1wt% of activator and 1wt% of mineral admixture.

[0065] Example 3

[0066] The only difference between this embodiment and Embodiment 1 is that a mine filling cement material that can cement high-doped phosphate tailings includes the following components, based on the mass of the mine filling cement material as 100wt%,: 40wt% of slag, 7wt% of kaolin, 10wt% of yellow phosphorus slag, 5wt% of phosphogypsum, 36wt% of cement clinker, 1wt% of activator and 1wt% of mineral admixture.

[0067] Example 4

[0068] The only difference between this embodiment and Embodiment 1 is that a mine filling cement material that can cement high-doped phosphate tailings includes the following components, based on the mass of the mine filling cement material as 100wt%,: 41wt% of slag, 7wt% of kaolin, 8wt% of yellow phosphorus slag, 2wt% of phosphogypsum, 36wt% of cement clinker, 1wt% of activator and 5wt% of mineral admixture.

[0069] Comparative Example 1

[0070] The difference between this comparative example and Example 1 is that in this comparative example, the phosphogypsum is only dried at 60°C and has a specific surface area of ​​60 m 2 / kg.

[0071] Comparative Example 2

[0072] The difference between this comparative example and Example 1 is that in this comparative example, only phosphogypsum and yellow phosphorus slag are used as cementing materials, and no slag, kaolin and cement clinker are added. A mine filling cement material that can cement high-doped phosphorus tailings, based on the mass of the mine filling cement material as 100wt%, includes the following components: 50wt% of yellow phosphorus slag, 44wt% of phosphogypsum, 5wt% of activator and 1wt% of mineral admixture.

[0073] According to the test mix ratio of the above examples 1-4 and comparative examples 1-2, the required materials: cement clinker, slag, kaolin, calcium hydroxide and aluminum sulfate are first weighed according to the ratio, mixed evenly for use, and then the tailings slurry with a concentration of 66% is weighed and stirred evenly, and then the weighed powder is poured into the mixing process at the same time. In order to simulate the actual situation of mine filling, the filling body is continuously stirred for 1 hour. After stirring, the filling body is loaded into a test mold of 40mm×40mm×160mm. The samples of examples 1-4 and comparative examples 1-2 are tested by the following experimental methods:

[0074] Expansion test method:

[0075] Referring to the national standard "GB / T 50080-2016 Standard for Test Methods of Ordinary Concrete Mixtures", place the expansion mold in the center of the glass plate, then pour the mixed slurry into the mold, scrape it flat with a scraper, and lift the expansion mold vertically upward at a slow and uniform speed. After waiting for 10 seconds, use a vernier caliper to measure the maximum diameters in two mutually perpendicular directions, and calculate the average of the two diameters.

[0076] Water bleeding rate test method:

[0077] According to the national standard "Concrete Admixture" (GB8076-2008), the stirred slurry is placed in a covered container to prevent water evaporation. In the first 60 minutes, use a pipette to suck out the seepage water every 10 minutes, and then suck out the water every 20 minutes until there is no seepage. 5 minutes before each water absorption, one side of the bottom of the cylinder should be raised for about 20 minutes to tilt the cylinder for easy water absorption. After water absorption, gently lay the cylinder flat and cover it. Pour the water sucked out each time into the stoppered measuring cylinder, and finally calculate the total water seepage, accurate to 1g, the calculation formula:

[0078]

[0079] Wherein, B is water seepage rate, in %;

[0080] Vw—total mass of water seepage, in grams (g);

[0081] W—water content of the mixture, in grams (g);

[0082] G—total mass of the mixture, in grams (g);

[0083] Gw—sample mass, in grams (g).

[0084] Maintenance method:

[0085] In order to simulate the temperature and humidity in the mine, the formed specimens were placed in a standard curing box with a designed temperature of 15±2℃ and a humidity of 80±5%.

[0086] Compressive strength:

[0087] According to the "Test Method for Cement Mortar Strength" (GB / T 17671-1999), the compressive strength of the filling body cured to the corresponding age was tested using the EMT504D microcomputer-controlled pressure test, and the loading speed of the compressive strength was 600N / s±50N / s.

[0088] The relevant data of Examples 1-4 and Comparative Examples 1-2 are summarized in Table 1 below:

[0089] Table 1. Relevant data of Examples 1-4 and Comparative Examples 1-2 (wt%)

[0090]

[0091] The relevant performance data of Examples 1-4 and Comparative Examples 1-2 are summarized in Table 2 below:

[0092] Table 2. Relevant performance data of Examples 1-4 and Comparative Examples 1-2

[0093]

[0094] The above embodiments and comparative examples are designed according to the filling requirements of a certain mine. In actual operation, the mortar-sand ratio can be adjusted according to the different strength requirements of different mines to achieve different required strengths.

[0095] The present invention provides a high-performance, low-cost, and environmentally friendly mine filling cement material by comprehensively utilizing phosphogypsum and phosphate tailings. The material not only solves the problem of waste disposal, but also improves the safety and stability of the mine, and has significant economic and social benefits.

[0096] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A mine filling cement material capable of cementing high-dosage phosphate tailings, characterized in that: Taking the mass of mine filling cement material as 100wt%, the invention comprises the following components: 40wt% to 45wt% of slag, 7wt% to 10wt% of kaolin, 8wt% to 10wt% of yellow phosphorus slag, 0wt% to 5wt% of phosphogypsum, 35wt% to 40wt% of cement clinker, 1wt% to 5wt% of activator and 1wt% to 5wt% of mineral admixture; the mineral admixture comprises bentonite, sepiolite and attapulgite.

2. The mine filling cement material capable of cementing high-dosage phosphate tailings according to claim 1, characterized in that: The specific surface area of ​​the phosphogypsum is ≥300m 2 / kg.

3. The mine filling cement material capable of cementing high-dosage phosphate tailings according to claim 1, characterized in that: The activator is at least two of sodium silicate, aluminum sulfate, calcium oxide and calcium hydroxide.

4. The mine filling cement material capable of cementing high-dosage phosphate tailings according to claim 3 is characterized in that: The activator is a combination of one of sodium silicate and aluminum sulfate and at least one of calcium oxide and calcium hydroxide.

5. The mine filling cement material capable of cementing high-dosage phosphate tailings according to claim 1, characterized in that: Based on 100wt% of the mineral admixture, the mineral admixture includes 15wt% to 25wt% of bentonite, 25wt% to 35wt% of sepiolite and 45wt% to 55wt% of attapulgite.

6. The mine filling cement material capable of cementing high-dosage phosphate tailings according to claim 1, characterized in that: The particle size of the component materials is ≥200 mesh, and the slag uses slag powder of S95 or above.

7. A method for preparing a mine filling cement material capable of cementing high-dosage phosphate tailings according to any one of claims 1 to 6, characterized in that: The steps include: S1: Pretreatment: flotation, washing and calcination of phosphogypsum; S2: mixing and grinding slag, metakaolin, yellow phosphorus slag, phosphogypsum and cement clinker to obtain a cementitious material; S2: 1wt% to 5wt% of an activator and 1wt% to 5wt% of a mineral admixture are mixed with a cementitious material and then ground to obtain a mine filling cement.

8. The method for preparing a mine filling cement material capable of cementing high-content phosphate tailings according to claim 7, characterized in that: In the step S1, the following specific steps are included: S1.1: Flotation: Mix phosphogypsum and water at a ratio of 1:2-3 to prepare a slurry, add a flotation agent, and feed it into a flotation machine. After multiple flotations, the solid and liquid are separated, and the filter cake is the preliminarily purified phosphogypsum; S1.2: Water selection: The phosphogypsum filter cake after flotation is mixed with water at a ratio of 1:2-3 to prepare a slurry, which is then washed with water for multiple times before solid-liquid separation. The filter cake is further purified phosphogypsum; S1.3: Calcination: The washed phosphogypsum filter cake is sent to a drying device for low-temperature drying at 100°C to 150°C to remove surface moisture. After drying to a moisture content of the phosphogypsum of less than 1%, it is sent to a calcining furnace for calcination at 600°C to 800°C for 1h to 2h, and then naturally cooled to room temperature to obtain the final purified phosphogypsum product.

9. The method for preparing a mine filling cement material capable of cementing high-content phosphate tailings according to claim 8, characterized in that: In the step S1.2, the water washing process is repeated several times until the soluble salt content in the phosphogypsum is ≤2%.

10. A method for using the mine filling cement material capable of cementing high-dosage phosphate tailings according to any one of claims 1 to 6, characterized in that: The steps include: T1: preparing the phosphate tailings into a phosphate tailings slurry with an underflow concentration of 66% to 68%; T2: mixing the mine filling cement material and the phosphate tailings slurry at a ratio of 1:7.2-8.8 to obtain a mixed filling material; T3: Sending mixed fill material into the mine.

Citation Information

Patent Citations

  • Low-bleeding-rate pumpable phosphogypsum and yellow phosphorus slag filling paste and preparation method of paste

    CN103964804A

Cited By

  • Yellow phosphorus slag-phosphogypsum-yellow phosphorus tailing mortar-based filling material as well as preparation method and application thereof

    CN120774685A